A guided dynamic programming approach for DNA sequence similarity search - Mohd Nordin Abdul Rahman (Fakulti Sains dan Teknologi, 2011)
DNA sequence similarity search is an important task in computational biology applications. Similarity search procedure is executed by an alignment process between query and targeted sequences. An optimal alignment process based on the dynamic programming algorithms has shown to have 0(n x m) time and space complexity. Heuristics algorithms can process a fast DNA sequence alignment, but generate low comparison sensitivity.